Scope of the ISO 14001: 2015 Standard as an Environmental Compliance Program - Martínez Reyes, Johana (Observatorio Medioambiental, 2020)
The inclusion of criminal liability of the legal person in the Spanish legal system turns out to be a highly debated issue that has led to the adoption of compliance programs in different business sectors. This ESTUDIO intends to identify the scope of the ISO 14001: 2015 Standard as an environmental compliance program, in order to verify if it may have any impact within the criminal process as an organization and management program that generates any circumstance of exemption or mitigation of the penalty, in accordance with the provisions of articles 31 and following of the Criminal Code - CP, taking into account that article 328 CP, establishes the penalties that the legal person will carry when they are responsible for the crimes contained in Chapter III Of the crimes against natural resources and the environment, of Title XVI Of crimes related to the planning of the territory and urban planning, the protection of historical heritage and the environment, of Book II CP. Likewise, the present research aims to analyze and assess unknown legal figures in the Colombian legal framework, such as compliance programs and criminal liability of the legal person; but also carry out a study of the content of the ISO 14001: 2015 Standard, as an environmental quality standard. The results obtained, allowed me to establish the causes and the requirements that would make the ISO 14001: 2015 Standard, an environmental compliance program that meets the requirements of the Spanish criminal regulations to be a suitable environmental organization and prevention model that could be considered within the criminal process as an exemption or mitigation of the criminal responsibility of the legal person.
Keywords: Compliance; ISO 14001:2015; Criminal Liability of the Legal Person; exemption and mitigation circumstances